The Influence of House Plants on Indoor CO2 - Sevik, Hakan; Cetin, Mehmet; Guney, Kerim; Belkayali, Nur (HARD Publishing Company, 2017)
This study aimed at determining the effect of carbon dioxide (CO2) in the internal environment of different indoor plants. Spathiphyllum (Spathiphyllum floribundum Schott), Yucca (Yucca elephantipes Regel), Dieffenbachia (Dieffenbachia amoena Gentil), and Ficus (Ficus benjamina L.) are frequently used in studies of indoor plants that examine light temperature depending on leaf surface and the effects of CO2 in the studied environment. As a result, decreases in CO2 were at the highest level in Ficus, and Dieffenbachia at 25 degrees C, followed by Spathiphyllum at 25 degrees C and Yucca at 20 degrees C. The amount of photosynthesis increased the leaf surface. For this reason, they reduced the amount of CO2 by increasing the amount of photosynthesis. The plant leaf surface was standardized, and calculations were made to meet the objective and the amount of CO2 in the local environment. Based on these calculations, it was determined that the greatest reduction of CO2 comes from the Ficus plant. In conclusion, the same layer as the surface are I m(2) leaf surface from Ficus benjamina on I m(3) without air vent in which the amount of CO2 in one hour could be reduced to about the level from 2,000 ppm at 25 degrees C 480.74 ppm and 408.08 ppm at 20 degrees C.
Keywords: 15. Life on land